Results of integrating short VR exercises into traditional CBTs - Richard Hannah (Association for Learning Technology, 2024)
The purpose of this research was to investigate the effects of short virtual reality (VR) exercises on knowledge retention for adult learners at a contractor safety training organisation supporting the energy industry who took computer-based training (CBT) courses. The intent was to simulate a delay period similar to that experienced by contractors who support work in the energy industry to determine if traditional CBT can be made more effective for stimulating greater transfer of learning with the addition of VR exercises. The experimental group was exposed to CBTs augmented by VR exercises that reinforced the CBT course learning objectives. The control group for this research took the same CBT course without short VR exercises. A quantitative analysis was performed on data collected from a course exam provided immediately after the course delivery and from a separate follow-up quiz delivered 3 days after the course(s) completion. Data from these testing instruments were analysed to determine the participant's likelihood of remembering content from the CBT courses and if there was greater knowledge retention of the course learning objectives and procedures within the experimental group than within the control group. The results found a non-statistically significant relationship between the two groups; however, trends between the groups show that there are benefits for transfer of learning when using short VR exercises compared to those groups without short VR exercises.